The impact of physical symptoms on depression and quality of life in patients with lung cancer: the moderating effects of illness perceptions and gender - Jinhuan Yang; Danni Dong; Gan He; Zhenghao Ge; Zhonglin Chen; Chenyan Han; Yi Zhao; Yaping He; Qiao Chu (Health and Quality of Life Outcomes)
Abstract Background Physical symptoms negatively affect lung cancer patients’ emotional well-being and quality of life. It remains understudied about what psychosocial factors may buffer the negative impact of physical symptoms. This study examines how illness perceptions moderate the impact of physical symptoms on depression and quality of life, and further considers gender differences. Methods A cross-sectional study was conducted on 316 lung cancer patients from Shanghai Chest Hospital in Shanghai, China, between July and September 2021. Participants completed questionnaires assessing physical symptoms, depression, quality of life, and illness perceptions. Results Hierarchical regression analyses revealed significant two-way interactions between physical symptoms and illness timeline perceptions on both depression (β = 0.12, P = 0.028) and quality of life (β = -0.13, P = 0.010). Additionally, significant three-way interactions involving physical symptoms, illness perceptions, and gender were found. Specifically, illness consequences perceptions interacted with physical symptoms and gender to predict depression (β = 0.17, P = 0.012), while personal control (β = 0.14, P = 0.022) and treatment control (β = 0.17, P = 0.017) interacted similarly to predict quality of life. Simple slope analyses indicated that positive illness perceptions alleviated the negative effects of physical symptoms on depression and quality of life, particularly in females. Conclusions These findings indicate that facilitating positive illness perceptions may buffer the adverse effects of physical symptoms on depression and quality of life. Personalized psychological interventions aimed at enhancing patients’ illness beliefs through positive psychological and behavioral strategies may contribute to improved coping and overall well-being.